Pemphigus and Pregnancy - Dipankar De; Shikha Shah; Rahul Mahajan; Sanjeev Handa (Indian Dermatology Online Journal, 2024)
Pemphigus in pregnancy is a special clinical scenario that has potential consequences on both maternal and fetal outcomes. Being an autoimmune disease with Th2 preponderance, pemphigus is expected to flare in pregnancy, especially in the first two trimesters. Fetal outcomes like stillbirth and neonatal pemphigus have been reported, the latter being a consequence of a transient transplacental transfer of autoantibodies. Management needs to be individualized keeping the risk/benefit ratios of therapies in mind while optimizing maternal and fetal health. It is crucial to have appropriate counseling regarding conception for women with pemphigus in the child-bearing period because the probability of adverse materno-fetal outcomes is higher if the disease is severe.